Some specific features of conjugate addition reactions with lithium and magnesium o-carborane derivatives - Kazantsev, A. V.; Otrashchenkov, E. A.; Aksartov, M. M. (Nauka/Interperiodica, 2004)
Reactions of lithium and magnesium o-carborane derivatives with ethyl alpha-nitrocinnamate, ethyl beta-(3-indolyl)-alpha-nitroacrylate, and diethyl m-nitrobenzylidenemalonate were studied. Some specific features of these reactions were established, and preparative methods for the synthesis of previously unknown o-carborane derivatives were developed.